The Other and Foreign Categories in Maria Konopnicka’s “Pan Balcer w Brazylii” - Kalinowski, Daniel (Migrations in the Slavic Cultural Space. From the Middle Ages to the Present Day, 2022)
The article concerns the descriptive poem by Maria Konopnicka Pan Balcer w Brazylii, which is interpreted in two anthropological categories: Other and Foreign. A leading role in the work of national awakening in Polish peasants is the factor that leads to the identification of identity motives: first a meeting and then a conflict between familiarity and otherness. The article discusses the relations between a Polish peasant and a German colonist, Polish Catholicism vs. “non-Polish” Protestantism, the Polish community vs. the black Brazilian community, the uniformity of the village cluster vs. the unrecognizability of Brazilian clusters. The description of Konopnicka’s work from the perspective of the category of literary anthropology leads to a postcolonial discourse, which – although not implemented in the foreground – is still visible in the projections and cultural complexes of the literary subject.